WHY HIV POSITIVE PATIENTS ON ANTIRETROVIRAL TREATMENT AND/OR COTRIMOXAZOLE PROPHYLAXIS USE TRADITIONAL MEDICINE: PERCEPTIONS OF HEALTH WORKERS, TRADITIONAL HEALERS AND PATIENTS: A STUDY IN TWO PROVINCES OF SOUTH AFRICA - Puoane, T R; Hughes, G D; Uwimana, Jan; Johnson, Q; Folk, W R (African Journal of Traditional, Complementary and Alternative Medicines, 2021)
The study explored the perceptions, knowledge and attitudes of patients, health workers and traditional healers about the use of traditional medicine and Anti Retroviral Therapy (ART). The study explored the perceptions, knowledge and attitudes of patients, health workers and traditional healers about the use of traditional medicine and Anti Retroviral Therapy (ART), using an exploratory qualitative design in two provinces of South Africa: an urban township health facility in the Western Cape, and a rural district hospital in KwaZulu-Natal (KZN) with antennal HIV rate of 32% and 28%’respectively. In-depth interviews were conducted with 14 participants: six HIV patients on ART and using Traditional Medicine(TM), two doctors, two nurses and four traditional healers. Two focus group discussions - one at each site - were held with community health workers who work with HIV-positive patients (Western Cape [5] and in KZN [4]). Patient said to have used Traditional Healing Practices (THP) before they were diagnosed with HIV, and some who have been diagnosed with HIV continue using TM in conjunction with ART and/or Cotrimoxazole prophylaxis. Patients preferred not to disclose THP to health professionals because of lack of support and understanding. Patients utilize THP because of family expectations, privacy and confidentiality, especially when they have not disclosed their HIV status. Healthcare professionals had strong negative opinions about THP, especially for HIV-positive patients. Traditional healers supported the patient’s rationale for THP use. This study revealed a need to better understand factors involved in patients’ choosing to use THP concurrently with ART.